TANTANGAN IMPLEMENTASI KONSEP ECO-SETTLEMENT DALAM UNDANG-UNDANG NO. 1 TAHUN 2011 TENTANG PERUMAHAN DAN KAWASAN PERMUKIMAN - Suryani, Anih Sri (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
Provision of quality housing and settlements is the basic right mandated by the Constitution. The enactment of Law No. 1 of 2011 on Housing and Settlements Area is the legal basis of housing maintenance and settlement areas in Indonesia. The concept of eco-settlement is a concept of ecologically developed from the concept of sustainable development. The concept harmonized the three pillars, namely social, economic, and ecological sustainability supported by established institution. Related to the concept of ecosettlement, the Law on Housing and Settlements Area accommodates several parameters in the concept, but some issues such as healthy and environmental friendly housing criteria, community education, community participation and institutional strengthening to be arranged in a more detailed regulations.